2022
DOI: 10.3390/su14084680
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of the COVID-19 Crisis on Hotel Industry Bankruptcy Risk through Novel Forecasting Models

Abstract: In this paper, we assess the impact of the COVID-19 crisis on the bankruptcy risk of a sample of 100 hotel companies and, consequently, on the hotel industry in the Republic of Serbia. The assessment applies to the period, 2019–2026, with the use of the data on the financial indicators for 2015–2020. Five novel structural time-series models, which have the indicators derived from Altman’s EM Z”-score model as predictors, were used, and a new conceptual framework for assessing bankruptcy risk is provided. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 109 publications
3
25
1
3
Order By: Relevance
“…Temelkov (2022), conducting research on the example of 34 international hotel chains and resorts, on the basis of financial reports for 2019 and 2020, determined that the onset of the COVID-19 pandemic in most hotels influenced the decline in income and the increase in the ratio of costs and income. Matejić et al (2022) confirmed with their research that the COVID-19 pandemic had negative consequences on the operations of companies from hotel industry in the Republic of Serbia. Conducting research on the example of 100 randomly selected hotel companies in the Republic of Serbia, using neural networks, it has been determined that an improvement in their financial position can be expected not before 2024, and even in 2026.…”
Section: Literature Review and Hypothesis Definitionsupporting
confidence: 52%
“…Temelkov (2022), conducting research on the example of 34 international hotel chains and resorts, on the basis of financial reports for 2019 and 2020, determined that the onset of the COVID-19 pandemic in most hotels influenced the decline in income and the increase in the ratio of costs and income. Matejić et al (2022) confirmed with their research that the COVID-19 pandemic had negative consequences on the operations of companies from hotel industry in the Republic of Serbia. Conducting research on the example of 100 randomly selected hotel companies in the Republic of Serbia, using neural networks, it has been determined that an improvement in their financial position can be expected not before 2024, and even in 2026.…”
Section: Literature Review and Hypothesis Definitionsupporting
confidence: 52%
“…The results showed that current liquidity, gross margin ratio, operating profitability of sales, and asset turnover are the most important explanatory factors in bankruptcy prediction. As declared by Matejic et al (2022), compared to the pre-COVID-19 period, the chance of bankruptcy will continue to be high, making the remaining businesses more susceptible to future exogenous developments. The specific interest in the manufacturing sector is presented in the research by Pacheco et al (2022), who also affirmed that estimates using financial information closest to the bankruptcy period could enhance the predictive power of the model.…”
Section: Research Resultsmentioning
confidence: 99%
“…Prvo, finansijska kriza 2008. godine, i drugo, finansijska i zdravstvena kriza kao rezultat virusa COVID-19 i pandemije koju je proglasila Svetska zdravstvena organizacija (Đekić et al, 2022, 36). Sektor turizma i ugostiteljstva je najviše pogođen nastankom pandemije (Mandarić et al, 2022;Matejić et al, 2022;Zhang et al, 2022). Usled propisanih mera za sprečavanje i/ili širenje virusa, poslovanje mnogih preduzeća iz ovog sektora je dovedeno u pitanje (Kalenjuk-Pivarski et al, 2021).…”
Section: Uvodunclassified